Impulse Buying Behavior terhadap Pakaian Adat Bali di Pesta Kesenian Bali tahun 2023 ditinjau dari Pengaruh Shopping Lifestyle dan Fashion Involvement - Anak Agung Elik Astari; Ni Wayan Ari Sudiartini (Departement of Mathematics Education, 2024)
Balinese traditional clothing is the most popular fashion stand at every arts festival in Bali, the newest models are always presented at this annual event, fashion transactions are the biggest transactions, this is partly due to the impulse buying behavior of the Balinese people, so this research aims to to find out: (1) the influence of shopping lifestyle on impulse buying behavior of traditional Balinese clothing (2) the influence of fashion involvement on impulse buying behavior of traditional Balinese clothing, and (3) the influence of shopping lifestyle and Fashion Involvement on impulse buying behavior of traditional Balinese clothing. This type of research is quantitative research. The population in this study were all visitors to the Bali Arts Festival (PKB) exhibition in 2023. The samples used were consumers who had purchased traditional Balinese clothing products at the Bali Arts Festival (PKB) exhibition. The sampling technique used in this research was purposive sampling, namely samples with criteria, with a sample size of 110 respondents. The data collection technique uses a questionnaire which has been tested for validity using and reliability testing using the Alpha Cronbach formula. The data analysis technique uses multiple regression tests. The research results show that: (1) There is a positive and significant influence of shopping lifestyle on impulse buying behavior of Balinese traditional clothing. This is shown by the t value of 6.228, t table of 0.1874, with a significance of 0.004. (2) there is a positive and significant influence of fashion involvement on impulse buying behavior of Balinese traditional clothing. This is shown from the calculated t value of 5.991 t table of 0.1874 with a significance of 0.004. (3) There is a positive and significant influence between shopping lifestyle and fashion involvement simultaneously on impulse buying behavior of Balinese traditional clothing. This is shown from the calculated t value of 5.991 t table of 0.1874 with a significance of 0.004.